1:3 ABAA sequence-regulated substituted polymethylenes via alternating radical copolymerization of methyl cinnamate and maleic anhydride followed by post-polymerization reactions. (November 2019) - Terao, Yuya; Sugihara, Shizuka; Satoh, Kotaro; Kamigaito, Masami
Graphical abstract: Highlights: Methyl cinnamate and maleic anhydride undergo 1:1 alternating radical copolymerization. The alternating copolymers are transformed into 1:3 sequence-regulated substituted polymethylenes. The rigid polymethylenes with one phenyl and three methyl ester groups show good thermal properties. RAFT enables molecular weight control and block copolymers with soft polyacrylates. Abstract: Methyl cinnamate (M1 ) and maleic anhydride (M2 ), which are both non-homopolymerizable 1, 2-disubtituted vinyl monomers, were radically copolymerized in toluene to result in 1:1 alternating copolymers. The 1:1 alternating sequence was confirmed by not only the monomer reactivity ratios obtained by using the terminal model fitted by the Kelen-Tüdõs method ( r 1 = 0.0035, r 2 = 0.069) but also MALDI-TOF-MS analysis of the copolymers with controlled molecular weights and relatively narrow molecular weight distributions ( M w / M n = 1.20), which were prepared by RAFT copolymerization using 2-cyano-2-propyl ethyl trithiocarbonate (CPETC) as the RAFT agent. The maleic anhydride unit was transformed into two methyl ester groups by hydrolysis followed by methylation. Since the propagation of methyl cinnamate occurred regioselectively via a styrenic radical, the methyl esterified copolymers possessed ABAA sequence-controlled substituted polymethylene structures (A: methyl ester, B: phenyl). The sequence-controlled substituted polymethylene showed good thermal properties ( T d5 = 323 °C, T g ≥ 192 °C) due to the rigid main-chain structures, which possessed a phenyl group on every fourth main-chain carbon in the repeating units in addition to three methyl ester groups on the other main-chain carbons. Block copolymers consisting of the rigid substituted polymethylene and soft poly(methyl acrylate) were also synthesized by RAFT polymerization.